Parenthood and the risk of diabetes in men and women: a 7- year prospective study of 0.5 million individuals - Peters, S; Yang, L; Woodward, M; Guo, Y; Chen, Y; Bian, Z; Millwood, I; Bragg, F; Zhou, X; Ge, P; Chen, B; Gao, Y; et al. (Springer, 2016)
Aims/hypothesis In women, higher parity has been associated with increased risk of diabetes later in life. It is unclear, however, whether this association is mainly due to biological effects of childbearing, or to socioeconomic and lifestyle factors associated with childrearing. We assessed the association between number of children and diabetes risk separately in women and men. Methods Between 2004 and 2008, the nationwide China Kadoorie Biobank recruited 0.5 million individuals aged 30–79 (mean 51 years) from ten diverse regions across China. During 7 years of follow-up, 8,840 incident cases of diabetes were recorded among 463,347 participants without prior cardiovascular diseases or diabetes. Multivariable Cox regression yielded sex-specific HRs and 95% CIs for incident diabetes by number of children. Results Overall,∼98% of all participants had children. In women, there was a J-shaped association between number of children and risk of diabetes. Compared with women with one child, the adjusted HRs for diabetes were 1.39 (95% CI 1.11, 1.73) for childless women, 1.12 (95% CI 1.07, 1.18) for those with two children, 1.23 (95% CI 1.16, 1.31) for those with three children, and 1.32 (95% CI 1.21, 1.44) for those with four or more children. In men, there was a similar association with risk of diabetes; the corresponding HRs were 1.28 (95% CI 1.02, 1.60), 1.19 (95% CI 1.12, 1.26), 1.32 (95% CI 1.21, 1.44) and 1.41 (95% CI 1.24, 1.60), respectively. In both sexes, the findings were broadly similar in different population subgroups. Conclusions/interpretation The similarity between women and men in the association between number of children and risk of diabetes suggests that parenthood is most likely to affect diabetes risk throughfactors associated with childrearing rather than via biological effects of childbearing.